EVALUATION OF PHYSICAL COMPOSITION OF ELDERS FROM GUARULHOS CITY (Fiep Bulletin - online, 2019)
Introduction: The increase of elders on Brazilian population enticed a discussion about life quality and degenerativediseases among this populationAbstractThe anthropometric variables from the physical composition evaluated were the BMI (body mass index), waistcircumference (WC), waist-hip ratio (WHR) and bodyfat percentage (BF%)In comparison to the waist-hip ratio (WHR) measurement, 34% of the elders were classified at very high risk. In thebody fat percentage test (BF%) 54% were classified as below average, bad or very bad presenting risk of acquiring chronicdegenerative diseasesObjective: Evaluate the physical composition of elders who were put on a physical activity program at the city ofGuarulhos.Materials and methodology: The population studied were elders over 60 years old, being 450 woman and 46 men,totaling 496 subjects who exercised twice a weekIntroduction: The increase of elders on Brazilian population enticed a discussion about life quality and degenerativediseases among this populationAbstractThe anthropometric variables from the physical composition evaluated were the BMI (body mass index), waistcircumference (WC), waist-hip ratio (WHR) and bodyfat percentage (BF%)In comparison to the waist-hip ratio (WHR) measurement, 34% of the elders were classified at very high risk. In thebody fat percentage test (BF%) 54% were classified as below average, bad or very bad presenting risk of acquiring chronicdegenerative diseasesObjective: Evaluate the physical composition of elders who were put on a physical activity program at the city ofGuarulhosResults: in relation to the BMI, 33% of the elders were obese, being that 44% of them were overweight and only 26% ofthem were at normal range. The WC measure showed that 48% of them were at very high risk. Only 24% were classified as lowrisk subjects. In comparison to the waist-hip ratio (WHR) measurement, 34% of the elders were classified at very high risk. In thebody fat percentage test (BF%) 54% were classified as below average, bad or very bad presenting risk of acquiring chronicdegenerative diseases. Conclusion: There are inadequacies on the anthropometry of the subjects, showing a prevalence in obesity, and thatmost of the body fat is located at the abdominal region, being that anatomic place that indicates a higher susceptibility on eldersondeveloping chronic degenerative non-transmissible diseases
Keywords: Health Services for the Aged; Anthropometry; Disability Evaluation.